Comments on "A metrics suite for object oriented design - Churcher, N.I.; Shepperd, M.J.; Chidamber, S.; Kemerer, C.F. (IEEE transactions on software engineering, 1995)
A suite of object oriented software metrics has recently been proposed by S.R. Chidamber and C.F. Kemerer (see ibid., vol. 20, p. 476-94, 1994). While the authors have taken care to ensure their metrics have a sound measurement theoretical basis, we argue that is premature to begin applying such metrics while there remains uncertainty about the precise definitions of many of the quantities to be observed and their impact upon subsequent indirect metrics. In particular, we show some of the ambiguities associated with the seemingly simple concept of the number of methods per class. The usefulness of the proposed metrics, and others, would be greatly enhanced if clearer guidance concerning their application to specific languages were to be provided. Such empirical considerations are as important as the theoretical issues raised by the authors.< >